A structural, morphological, linear, and nonlinear optical spectroscopic studies of nanostructured Al-doped ZnO thin films: An effect of Al concentrations. Issue 8 (18th February 2019) - Arif, Mohd; Shkir, Mohd; AlFaify, Salem; Ganesh, Vanga; Sanger, Amit; Algarni, Hamed; Vilarinho, Paula M.; Singh, Arun
Abstract: Abstract : Sol–gel spin coating is applied to fabricate the pure and different concentrations of aluminum (Al)-doped ZnO films on high-quality silicon substrates. All films are showing high crystallinity in X-ray diffraction study, and lattice constants were obtained using PowderX software. The value of crystallite size was found in range of 20–40 nm. EDX/SEM mapping was performed for 2 wt% Al-doped ZnO film, which shows the presence of Al and its homogeneous distribution in the film. SEM investigation shows nanorods morphology all over the surface of films, and the dimension of nanorods is found to increase with Al doping. The E (g)dire. values were estimate in range of 3.25–3.29 eV for all films. Linear refractive index was found in range of 1.5–2.75. The χ 1 value is found in range of 0.13–1.4 for all films. The χ 3 values are found in range of 0.0053 × 10 −10 to 6.24 × 10 −10 esu for pure and doped films. The n 2 values were also estimated. These studies clearly showed that the properties of ZnO have been enriched by Al doping, and hence doped films are more appropriate for optoelectronic applications.